Microemulsion interface model for chemical enhanced oil recovery design - Hon, V.Y. (Elsevier B.V., 2022)
The surfactant phase behavior laboratory test for chemical enhanced oil recovery (EOR) formulation design is time consuming. However, it is possible to use computational chemistry simulation to minimize the duration. The only known non-empirical approach to predict surfactant phase behavior is by surface tension analysis, but the optimum phase behavior boundary is unclear and its applicability in actual complex crude oil is unproven. This research overcomes these issues by developing a microemulsion interface model using digital oil model with accurate representation of atomistic components of actual crude oil as inputs to the simulation. The microemulsion interface model is developed based on physical chemistry of surface tension and torque concepts coupled with solution of interface bending rigidity in relation to surfactant solubilization and interface energy. The model is implemented in coarse-grained molecular dynamics simulation technique. The microemulsion interface model is verified with surfactant phase behavior laboratory data using actual crude oil. Good agreement for 12 out of 14 chemical EOR formulations between simulations and phase behavior laboratory results is achieved. This indicates that the main characteristics and physics of the formation of optimal microemulsion were captured correctly in the microemulsion interface model. The duration for surfactant phase behavior determination can be reduced from 14 days in laboratory down to 1.5 day by using the microemulsion interface model, resulting in 90-time reduction. This faster and more informed formulation development process can minimize time and costly resources as chemical EOR formulations proceed into field implementation. Â© 2022 Elsevier B.V.